NEW METHODS OF OPTIMIZATION OF PROCESSES OF FRICTION IN THE BRAKE MECHANISMS OF BORING OPTIONS - Криштопа, Людмила Іванівна; Криштопа, Святослав Ігорович; Прунько, Ігор Богданович; Богатчук, Іван Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The perspective direction of rise of efficiency of drill units is represented at the expense of automation of processes of braking of drilling hoists on the basis of wide implantation of electronic and computer technologies. The setting of the task is fulfilled and the principles of constructing of the atomized brake assemblies are formulated. A ground of the proposed approach is the complex application of electronic devices for optimization of the process of braking at execution of elevation.